Vinyltriazine porous organic polymer synthesized based on sonochemical method and preparation method and application thereof
The rapid synthesis of vinyl triazine porous organic polymers by acoustic chemistry method solves the problem of long production in the prior art, achieves efficient and rapid large-scale production, and has ultra-high photocatalytic activity and stability.
Patent Information
- Application Number
- CN202411529905.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The existing preparation method of vinyl triazine porous organic polymers takes a long time and is difficult to prepare quickly and large-scale, which limits its application in photocatalytic decomposition of water to produce hydrogen.
The vinyl triazine porous organic polymer was synthesized by acoustic chemistry method, and rapid synthesis was achieved by reacting the aldehyde monomer and nitrile monomer containing triazine under ultrasonic action.
This method does not require inert gas assistance, has a fast reaction, and can produce high-performance and high-stability photocatalysts on a large scale, showing ultra-high photocatalytic activity and stability.
Smart Images

Figure CN119409945A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic polymer compounds, and in particular relates to a vinyl triazine porous organic polymer synthesized based on a sonochemical method, and a preparation method and application thereof. Background Art
[0002] In the past few decades, the increasingly severe energy consumption and environmental pollution problems have become a huge challenge for sustainable development. Hydrogen energy is considered to be an ideal clean energy source due to its carbon-free and high energy density. The technology of catalyzing water decomposition by light irradiation of photocatalytic materials converts inexhaustible solar energy into hydrogen energy, which is a promising way to solve the above problems. Among the various photocatalytic materials, porous organic polymers have attracted much attention due to their advantages such as large specific surface area, low density and uniform pore size.
[0003] At present, the research on porous organic polymer photocatalysts is more focused on materials connected by imine bonds. However, the imine bond has poor chemical stability, is easily hydrolyzed under acidic conditions, and the weak electron delocalization caused by its strong polarization property is not conducive to photocatalytic reaction. Recently, the preparation of vinyl porous organic polymers connected by carbon-carbon double bonds by Knoevenagel condensation reaction has attracted widespread attention. Compared with imino porous organic polymers, vinyl porous organic polymers show excellent chemical stability and excellent electron delocalization. In particular, vinyl triazine porous organic polymers, due to the unique electron transfer properties of triazine rings, show excellent photocatalytic water decomposition and hydrogen production performance (e.g., CN 117510799 A). However, vinyl triazine porous organic polymers are currently mainly synthesized by solvothermal method. Although such methods can accurately control the synthesis process, the preparation process is time-consuming and difficult to prepare on a large scale quickly, which limits its application. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a vinyl triazine porous organic polymer synthesized based on a sonochemical method and a preparation method and application thereof in view of the deficiencies in the prior art. The vinyl triazine porous organic polymer exhibits ultra-high photocatalytic activity and stability in photocatalytic water decomposition to produce hydrogen, and its preparation method does not require the assistance of inert gas, has a fast reaction, and is conducive to large-scale production and preparation.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A vinyl triazine porous organic polymer synthesized based on a sonochemical method is synthesized from an aldehyde monomer and a nitrile monomer containing triazine through a sonochemical method.
[0007] According to the above scheme, the triazine-containing aldehyde monomer is 2,4,6-tris(4-aldehydephenyl)-1,3,5-triazine or 4',4"',4"'-(1,3,5-triazine-2,4,6-triyl)tris(([1,1'-biphenyl]-4-carboxaldehyde)).
[0008] According to the above scheme, the nitrile monomer is terephthalonitrile, 2,2'-([1,1'-biphenyl]-4,4'-diyl)diacetonitrile, 2,2'-([1,1':4',1"-terphenyl]-4,4"-diyl)diacetonitrile, 2,2',2"-(benzene-1,3,5-triyl)triacetonitrile or 1,3,5-tris(4-cyanomethylbenzene)benzene.
[0009] According to the above scheme, the vinyl triazine porous organic polymer has a network structure or a nanosphere structure obtained by stacking nanowires.
[0010] The present invention also includes a sonochemical synthesis method for the above-mentioned vinyl triazine porous organic polymer, and the specific steps are as follows: an aldehyde monomer containing triazine, a nitrile monomer, a catalyst and a solvent are added to a reaction container, and then the reaction container is placed in an ultrasonic machine to perform a sonochemical synthesis reaction in an air atmosphere. After the reaction is completed, the obtained reaction liquid is post-treated to obtain a vinyl triazine porous organic polymer.
[0011] According to the above scheme, the catalyst is selected from at least one of cesium carbonate, sodium hydroxide or potassium hydroxide.
[0012] According to the above scheme, when the nitrile monomer is terephthalonitrile, 2,2'-([1,1'-biphenyl]-4,4'-diyl)diacetonitrile or 2,2'-([1,1':4',1"-terphenyl]-4,4"-diyl)diacetonitrile, the molar ratio of the aldehyde monomer containing triazine, the cyano monomer and the catalyst is 1:1.5:1-6; when the nitrile monomer is 2,2',2"-(benzene-1,3,5-triyl)triacetonitrile or 1,3,5-tris(4-cyanomethylbenzene)benzene, the molar ratio of the aldehyde monomer containing triazine, the cyano monomer and the catalyst is 1:1:1-6.
[0013] According to the above scheme, the solvent is a mixed solvent of o-dichlorobenzene and n-butanol, and the volume ratio of o-dichlorobenzene to n-butanol is 0.8-4:1.
[0014] According to the above scheme, the mass volume ratio of the triazine-containing aldehyde monomer to the solvent is 10-20 mg / mL.
[0015] According to the above scheme, the sonochemical synthesis reaction conditions are: ultrasonic frequency of 20 to 60 kHz, temperature of 5 to 25° C., and ultrasonic time of 3 to 6 hours.
[0016] According to the above scheme, the post-treatment method is: centrifuging the obtained reaction solution, washing the obtained solid product with one or more solvents in sequence, and finally washing with water, and then drying.
[0017] According to the above scheme, the solvent is selected from one or more of acetone, tetrahydrofuran, ethanol, methanol, and dichloromethane.
[0018] The present invention also includes the use of the vinyl triazine porous organic polymer synthesized based on the sonochemical method as a photocatalyst in photocatalytic water decomposition.
[0019] According to the above scheme, the rate of hydrogen production by photocatalytic water decomposition of the vinyl triazine porous organic polymer synthesized based on the sonochemical method is 10 to 200 mmol / h / g.
[0020] The beneficial effects of the present invention are:
[0021] (1) The vinyl triazine porous organic polymer synthesized by the sonochemical method of the present invention has an ultra-high photocatalytic hydrogen production performance, and the material has good stability and is not easily decomposed in the photocatalytic water decomposition hydrogen production reaction, thus overcoming the disadvantage of the instability of porous organic polymer photocatalysts such as imino groups in the past.
[0022] (2) The preparation method of the present invention does not require the assistance of an inert atmosphere and can be synthesized simply and quickly by sonochemical method. The steps are simple and can be used to quickly and large-scale prepare photocatalysts with both high performance and high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a field emission scanning electron microscope image of the vinyl triazine porous organic polymer TFPT-PDAN prepared in Example 1 of the present invention;
[0024] Figure 2 This is a field emission scanning electron microscope image of the vinyl triazine porous organic polymer TFPT-BTAN prepared in Example 2;
[0025] Figure 3 The Fourier transform infrared spectrum of the vinyl triazine porous organic polymer TFPT-PDAN and its constituent monomers prepared in Example 1;
[0026] Figure 4 The Fourier transform infrared spectrum of the vinyl triazine porous organic polymer TFPT-BTAN prepared in Example 2 and its constituent monomers;
[0027] Figure 5 This is a comparison chart of the photocatalytic water decomposition and hydrogen production performance of the vinyl triazine porous organic polymer prepared in Examples 1 and 2;
[0028] Figure 6This is a test diagram of the photocatalytic water decomposition and hydrogen production cycle performance of TFPT-PDAN prepared in Example 1;
[0029] Figure 7 This is a field emission scanning electron microscopy image of the TFPT-PDAN prepared in Example 1 after a 15-hour cycle experiment;
[0030] Figure 8 This is the Fourier transform infrared spectrum of TFPT-PDAN prepared in Example 1 before and after a 15-hour cycle experiment. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below using embodiments and in conjunction with the accompanying drawings. However, it should be understood that the embodiments are for better explanation of the present invention and are not intended to limit the present invention.
[0032] Example 1
[0033] A vinyl triazine porous organic polymer is prepared by a sonochemical synthesis method. The specific synthesis steps are as follows: 29.8 mg of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine (0.076mmol), 17.8mg terephthalonitrile (0.114mmol), 74.3mg cesium carbonate (0.228mmol), 9mL o-dichlorobenzene and 11mL n-butanol were added, and then the reagent bottle was placed in an ultrasonic machine for ultrasonic reaction in an air atmosphere. The ultrasonic frequency was 40kHz, the ultrasonic time was 3 hours, and the temperature was 25°C. After the reaction was completed, the reaction was centrifuged, and the solid product was washed with acetone, tetrahydrofuran, ethanol and water in sequence until the filtrate was colorless. The product was then transferred to a 50mL centrifuge tube and evenly dispersed with 5mL water. The centrifuge tube was placed in liquid nitrogen and frozen for 5min, and then the centrifuge tube was transferred to a freeze dryer and freeze-dried at -50°C for 36h to obtain a vinyl triazine porous organic polymer named TFPT-PDAN.
[0034] The synthetic route is as follows:
[0035]
[0036] Figure 1 This is a field emission scanning electron microscope image of the vinyl triazine porous organic polymer TFPT-PDAN prepared in this example. It can be seen that its microscopic morphology is a network structure formed by accumulation of nanowires.
[0037] Figure 3The Fourier transform infrared spectra of the vinyl triazine porous organic polymer TFPT-PDAN prepared in this example and its constituent monomers show that for TFPT-PDAN, there are two peaks (2820 cm -1 and 2731cm -1 ) has disappeared, and the signal peak of C=O stretching vibration (1700cm -1 ) decreased significantly, indicating that the aldehyde group underwent a condensation reaction, and the signal peak of C≡N stretching vibration in TFPT-PDAN increased from 2249 cm -1 Move to 2218cm -1 , indicating that the chemical environment of C≡N has changed, further proving that the Knoevenagel condensation reaction has successfully occurred to form vinyl cyanide.
[0038] Example 2
[0039] A vinyl triazine porous organic polymer is prepared by a sonochemical synthesis method. The specific synthesis steps are as follows: 29.8 mg 2,4,6-tris (4-formylphenyl)-1,3,5-triazine (0.076 mmol), 14.8 mg 2,2',2"-(Benzene-1,3,5-triyl)triacetonitrile (0.076mmol), 74.3mg (0.228mmol) cesium carbonate, 9mL o-dichlorobenzene and 11mL n-butanol, then put the reagent bottle into an ultrasonic machine, and ultrasonically react under air atmosphere, the ultrasonic frequency is 40kHz, the temperature is 25℃, and the ultrasonic time is 3 hours. After the reaction, the obtained product is washed with acetone, tetrahydrofuran, ethanol and water in sequence until the filtrate is colorless, and then the product is transferred to a 50mL centrifuge tube, dispersed evenly with water, and the centrifuge tube is placed in liquid nitrogen for freezing for 5min, and then the centrifuge tube is transferred to a freeze dryer and freeze-dried at -50℃ for 36h to obtain a vinyl triazine porous organic polymer named TFPT-BTAN.
[0040] The synthetic route is as follows:
[0041]
[0042] Figure 2 The field emission scanning electron microscope image of the vinyl triazine porous organic polymer TFPT-BTAN prepared in this example shows that its microscopic morphology is a nanosphere structure of different sizes.
[0043] Figure 4 The Fourier transform infrared spectra of the vinyl triazine porous organic polymer TFPT-BTAN prepared in this example and its constituent monomers are shown in Figure 1. Figure 3By contrast, the same logic can be used to prove that the Knoevenagel condensation reaction successfully occurred and vinyl cyanide was formed.
[0044] Photocatalytic activity test: The photocatalytic water decomposition hydrogen production performance experiment was carried out in an all-glass automatic online trace gas analysis system (Labsolar-6A, Beijing Bofeilai, China), using a 300W xenon lamp as the irradiation light source. During the experiment, 5 mg of the vinyl triazine porous organic polymer prepared in Example 1 or 2 was first weighed and added to 15 mL of N, N-dimethylformamide, and ultrasonically dispersed for 10 min to disperse it evenly to obtain solution A. Another 0.88 g of ascorbic acid was weighed and added to 35 mL of water, and ultrasonically dispersed for 10 min to disperse it evenly to obtain solution B. Solution B was added to A, stirred for 5 min, and then 13.5 μL of hexahydrate chloroplatinic acid aqueous solution (10 g / L) was added, and ultrasonically dispersed for 10 min to obtain a reaction solution, and then the obtained reaction solution was transferred to the reactor of Labsolar-6A. Before irradiation, the reactor was first evacuated to 1.0 kPa, and then helium was flushed to 80.0 kPa, three times in a row, to completely remove the air and dissolved oxygen in the reaction system. During the illumination test, the generated gas was analyzed once every 1 hour using a gas chromatograph.
[0045] Figure 5 The photocatalytic performance comparison of water decomposition and hydrogen production obtained by the above-mentioned photocatalytic activity test of the vinyl triazine porous organic polymer prepared in Examples 1 and 2 shows that the hydrogen production rate of TFPT-PDAN is as high as 191.5 mmol h -1 g -1 The hydrogen production rate of TFPT-BTAN is 11.1 mmol h -1 g -1 .
[0046] Cyclic stability test: The reaction solution was prepared by the above-mentioned photocatalytic activity test method and the air and dissolved oxygen in the reaction system were thoroughly removed before illumination. During the illumination test, the generated gas was analyzed once every 1 hour of illumination. Every 3 hours of illumination, the catalyst vinyl triazine porous organic polymer was filtered out from the reaction solution, and the above test was repeated after the reaction solution was reconfigured, for a total of 5 tests.
[0047] Figure 6 This is a test diagram of the photocatalytic water decomposition and hydrogen production cycle performance of TFPT-PDAN prepared in Example 1. It can be seen that in the 15-h cycle experiment, the photocatalytic water decomposition and hydrogen production rate of TFPT-PDAN did not decrease substantially, confirming its excellent stability.
[0048] Figure 7This is a field emission scanning electron microscope image of the TFPT-PDAN prepared in Example 1 after a 15-hour cycle experiment. Figure 8 The Fourier transform infrared spectra of TFPT-PDAN prepared in Example 1 before and after a 15-hour cycle experiment show that the morphology and chemical structure of TFPT-PDAN have basically not changed after 15 hours of reaction, further proving its excellent stability.
Claims
1. A vinyl triazine porous organic polymer synthesized based on sonochemical method, characterized in that: The invention is synthesized from an aldehyde monomer and a nitrile monomer containing triazine by a sonochemical method.
2. The vinyl triazine porous organic polymer synthesized by sonochemical method according to claim 1, characterized in that: The triazine-containing aldehyde monomer is 2,4,6-tris(4-aldehyde phenyl)-1,3,5-triazine or 4',4'',4''-(1,3,5-triazine-2,4,6-triyl)tris(([1,1'-biphenyl]-4-carboxaldehyde)).
3. The vinyl triazine porous organic polymer synthesized based on sonochemical method according to claim 1, characterized in that: The nitrile monomer is terephthalonitrile, 2,2'-([1,1'-biphenyl]-4,4'-diyl)diacetonitrile, 2,2'-([1,1':4',1"-terphenyl]-4,4"-diyl)diacetonitrile, 2,2',2"-(benzene-1,3,5-triyl)triacetonitrile or 1,3,5-tris(4-cyanomethylbenzene)benzene.
4. The vinyl triazine porous organic polymer synthesized based on sonochemical method according to claim 1, characterized in that: The vinyl triazine porous organic polymer has a network structure or a nanosphere structure obtained by stacking nanowires.
5. The sonochemical synthesis method of the vinyl triazine porous organic polymer according to any one of claims 1 to 4, characterized in that: The specific steps are as follows: adding an aldehyde monomer containing triazine, a nitrile monomer, a catalyst and a solvent into a reaction container, then placing the reaction container into an ultrasonic machine, and performing a sonochemical synthesis reaction under an air atmosphere. After the reaction is completed, the obtained reaction liquid is post-treated to obtain a vinyl triazine porous organic polymer.
6. The sonochemical synthesis method of vinyl triazine porous organic polymer according to claim 5, characterized in that: The catalyst is selected from at least one of cesium carbonate, sodium hydroxide or potassium hydroxide.
7. The sonochemical synthesis method of vinyl triazine porous organic polymer according to claim 5, characterized in that: When the nitrile monomer is terephthalonitrile, 2,2'-([1,1'-biphenyl]-4,4'-diyl)diacetonitrile or 2,2'-([1,1':4',1"-terphenyl]-4,4"-diyl)diacetonitrile, the molar ratio of the aldehyde monomer containing triazine, the cyano monomer and the catalyst is 1:1.5:1-6; when the nitrile monomer is 2,2',2"-(benzene-1,3,5-triyl)triacetonitrile or 1,3,5-tris(4-cyanomethylbenzene)benzene, the molar ratio of the aldehyde monomer containing triazine, the cyano monomer and the catalyst is 1:1:1-6.
8. The sonochemical synthesis method of vinyl triazine porous organic polymer according to claim 5, characterized in that: The solvent is a mixed solvent of o-dichlorobenzene and n-butanol, and the volume ratio of o-dichlorobenzene to n-butanol is 0.8-4:1; the mass volume ratio of the aldehyde monomer containing triazine to the solvent is 10-20 mg / mL.
9. The sonochemical synthesis method of vinyl triazine porous organic polymer according to claim 5, characterized in that: The sonochemical synthesis reaction conditions are as follows: ultrasonic frequency is 20 to 60 kHz, temperature is 5 to 25° C., and ultrasonic time is 3 to 6 hours.
10. Use of the vinyl triazine porous organic polymer synthesized by sonochemical method as claimed in any one of claims 1 to 4 as a photocatalyst in photocatalytic water decomposition.
Citation Information
Patent Citations
Covalent organic framework material as well as preparation method and application thereof
CN117510799A